Improvement in Estimated Glomerular Filtration Rate in Patients with Chronic Kidney Disease Undergoing Catheter Ablation for Atrial Fibrillation. (26th September 2014) - NAVARAVONG, LEENHAPONG; BARAKAT, MICHEL; BURGON, NATHAN; MAHNKOPF, CHRISTIAN; KOOPMANN, MATTHIAS; RANJAN, RAVI; KHOLMOVSKI, EUGENE; MARROUCHE, NASSIR; AKOUM, NAZEM
AF Ablation and eGFR Introduction Chronic kidney disease (CKD) and atrial fibrillation (AF) often coexist. We studied the association of CKD with atrial fibrosis and the effect of AF ablation on kidney function. Methods AF patients who had a pre‐ and postablation serum creatinine and who completed a late gadolinium enhancement cardiac magnetic resonance imaging (MRI; LGE‐MRI) prior to ablation were included. Estimated glomerular filtration rate (eGFR) was calculated and CKD was staged using the National Kidney Foundation guidelines. Patients with eGFR <30 mL/min/1.73 m2 were excluded. LGE‐MRI was used to quantify atrial fibrosis. Patients were followed for recurrence and change in eGFR. Results A total of 392 patients were included in the study. A total of 118 (30.2%) had CKD stage 1, 198 (50.4%) CKD stage 2, 56 (14.3%) CKD stage 3A, and 20 (5.1%) CKD stage 3B. Patients with advanced CKD were more likely to be male and to have cardiovascular disease. Atrial fibrosis was not significant different between included CKD stages: 15.8 ± 8.8%, 16.6 ± 12.1%, 17.1 ± 10.4%, and 16.5 ± 8.4% for CKD stage 1, 2, 3A, and 3B, respectively (P = 0.476). At a median of 115 days following ablation, eGFR increased significantly in CKD stage 2 (74 ± 9 to 80 ± 23; P = 0.04), 3A (53 ± 5 to 69 ± 24; P < 0.001), and 3B (40 ± 4 to 71 ± 28; P < 0.01) and decreased in CKD stage 1 (109 ± 18 to 82 ± 28; P < 0.001). Arrhythmia recurrence was associated with atrial fibrosis (hazard ratio [HR] = 1.04, P < 0.01) and persistent AF (HR = 1.5; P = 0.04) but not with CKD stage (HR = 0.98; P = 0.89). Conclusions Restoring sinus rhythm with ablation leads to significant improvement of renal function in patients with chronic kidney disease.